USING KAHOOT TO INCREASE STUDENTS’ ENGAGEMENT AND ACTIVE LEARNING: A GAME BASED TECHNOLOGY TO SENIOR HIGH SCHOOL STUDENT - Veronika Heni; Sudarsono Sudarsono; Regina Regina (ICoTE Proceedings, 2019)
Students, particularly in senior high school often state that they like instructors who employ active learning strategies to get students engaged with the class topic. Sometimes, large teaching classes are difficult to get students to participate in classroom activities and assess whether they are truly learning or not. It is why providing a game is an appropriate way to create a fun and interactive engagement for students to learn and comprehend the information. “The value of games as a vehicle for teaching concepts while inspiring students is now well accepted at almost all levels of education” Becker  (2001). Kahoot is known as a technology-based instructional tool, it is a popular eLearning tool that easily can be used to add vitality, student engagement, and meta-cognitive supports with limited instructor or student training required. This study aims to analyze the use of Kahoot in engaging students’ active response in learning English. This is a classroom action research. Descriptive analysis is conducted to gain the students action and response during teaching and learning processes proposed by Kemmis and McTaggart in Hopkins (2008). The subjects of this study are twelve grade students of SMAN 1 Serawai, Kabupaten Sintang.